One night with Cinderella - Bryant, Niobia (Harlequin desire, 2021)
"Gabriel Cress is heir to his family's restaurant empire--and is expected to behave as such. Not seduce the housekeeper. But beneath Monica Darby's shy exterior is a siren who makes the jaded New Yorker burn for more. But when Gabe's meddling family and a surprise inheritance raise doubts he can't ignore, will the clock strike twelve on their budding affair?" -- Page [4] cover.